Teaching and Researching Women’s and Gender Studies in Post-apartheid South Africa - Deirdre Byrne (Gender a Výzkum)
This article argues that South African universities experience a variety of constraints upon their freedom to teach and conduct research. These restrictions affect all academic disciplines, including women’s and gender studies. The hegemony of neoliberalism affects the formation of collective and individual subjectivities. Its cultural operations possess the power to privilege and promote concepts that serve its monetary goals, while suppressing those that do not. Unfortunately, the managerialist turn in universities has meant that courses and units that are perceived as profitable receive funding, while those that are perceived as unprofitable do not. Women’s and gender studies tends to be a casualty of the neoliberal approach to higher education, with university managements allocating some funding to its operations, but frequently not enough to allow these units to flourish. This often becomes a self-reinforcing situation, where the university management claims that the unit in question is not successful, and then cuts funding, which further curtails operations. Consequently, women’s and gender studies units in South African universities remain marginalised, despite their potential to destabilise heteropatriarchal hegemonies.